Implementasi pendidikan santriprenure di Pondok Pesantren Kebudayaan Surau Kami Kota Semarang - Zaenal Abidin; Rina Priarni; Ita Wijayanti (At Turots: Jurnal Pendidikan Islam, 2023)
Santri tend not to be ready to be involved in society when they graduate from Islamic boarding schools because of their low knowledge of entrepreneurial spirit, they only focus on religious studies. This study aims to explore these problems, including: 1) Knowing the Surau Kami Islamic Boarding School before the santripreneur program was carried out 2) Knowing the santripreneur entrepreneurship program through the santripreneurs at the Surau Kami Cultural Islamic Boarding School, Pedalangan Banyumanik Village, Semarang. The type of research used is the Participatory Action Research (PAR) method, namely research with a direct participatory action research approach. Information in this study was obtained through observation, interviews and documentation through two types of data sources, namely primary data and secondary data. This study describes social phenomena that are carried out through participatory action research or (PAR) on entrepreneurial activities for students to take action to improve the economy. The benefit of this research is that there is an entrepreneurial spirit education in the students, so that they are ready to join the community when they graduate from the Cultural Islamic Boarding School, Surau Kami, Pedalangan Banyumanik Village, Semarang.